The sublime object of ideology - Žižek, Slavoj (London : Verso, 2008)
Slavoj Žižek presents a provocative and original examination of the question of human agency in a postmodern world.
How did Marx invent the symptom --
From symptom to Sinthome --
'Che Vuoi?' --
You only die twice --
Which subject of the real? --
'Not only as substance, but also as subject.'
includes index
ENH
Trim Education
Keywords: Ideology; Fantasy; Popular culture